Implementasi Regulasi Taukil Wali Berdasarkan PMA Nomor 20 Tahun 2019 (Studi Kasus di KUA Kecamatan Cimalaka Kabupaten Sumedang) - Rizal Firdaus; Fitri Samrotul Puadah; Widya Nurul Hasni; Siti Robiatul Adawiyah; Syifa Febriana Nurul Wildain (Penerbit Lestari Sakha Pustaka, 2026)
Taukil wali is a mechanism for delegating marriage guardianship rights to another party, regulated under Article 12 paragraphs (4) and (5) of the Minister of Religious Affairs Regulation (PMA) Number 20 of 2019 concerning Marriage Registration. This study aims to analyze the implementation mechanism of taukil wali regulation at the Office of Religious Affairs (KUA) of Cimalaka Subdistrict, Sumedang Regency, identify supporting and inhibiting factors, and examine its conformity with Islamic law and prevailing legislation. This research employs a qualitative method with a juridical-empirical approach through in-depth interviews, observation, and documentation. The findings reveal that the taukil wali mechanism at KUA Cimalaka has procedurally complied with PMA Number 20 of 2019, encompassing marriage registration, document examination, preparation of the taukil wali letter before the Head of KUA according to the guardian's domicile witnessed by two witnesses, and the execution of the marriage contract by the representative guardian. Supporting factors include regulatory clarity, competence of religious marriage officers, and advancement of communication technology, while inhibiting factors encompass low legal awareness among the community, geographical-administrative constraints, and Sundanese socio-cultural factors. Substantively, the practice conforms to Islamic legal principles agreed upon by four schools of jurisprudence and supported by the principle of dar' al-mafasid muqaddam 'ala jalb al-mashalih, yet procedural inconsistencies persist, particularly the use of judge guardians without first pursuing the taukil wali mechanism. This study recommends intensifying socialization of taukil wali regulations and strengthening inter-KUA coordination.